REMONOR : Résultats 2002. Evaluation de la mortalité, croissance et qualité des huîtres creuses - Simonne, Charlotte; Pien, S; Hugonnet, Virginie; Le Gagneur, Eric; Ropert, Michel; Kopp, Joel; Richard, O (2003)
The national REMORA network is targeted on the studies of growth, flesh quality and mortality of a sample of cupped oyster Crassostrea gigasdistributed on 9 stations along the coast of Normandy. As a better precision is needed for regional purpose, 7 new stations have been added. A total number of 16 stations is now sampled from Chausey to Meuvaines. Weak rates of mortality have been noticed in 2002 on both adults (7%) and spat (6 %). These rates are the weakest ever seen. The mortality rates in the Baie des veys were less than 10 %. This rearing area shows usually a much higher mortality level. Growth rates were noticed weaker than usual. They slowly decline from 1999. From Mach to December, the growth rate of adults has been computed to 0,21 %/day (for a final weigh reaching 59,9 g). This rate is the weakest ever met since the beginning of REMORA's study in 1998. The shell's filling up is relatively constant compared to previous years, up to 11 %. The infestation by worms, genus Polydora, has been noticed to be in light decreasing since 1999. Confirmation has been brought in 2002. L'ajout de stations à vocations régionales en 1998 au suivi national REMORA d'évaluation de la mortalité et de la croissance et de la qualité des huîtres creuses a permis de mieux cerner la problématique normande sur ce sujet. Au total, seize points sont suivis de Meuvaines à Chausey. L'année 2002 se distingue par un faible taux de mortalité pour les adultes (7%) comme pour les juvéniles (6%). Ces taux sont les plus faibles depuis le début du réseau REMONOR. La Baie des Veys, souvent sujette à des mortalités estivales, présente des taux inférieurs à 10% sur cette période. Par ailleurs, la croissance est plus faible que l'année précédente. En fait, les taux de croissance diminuent depuis 1999. Entre mars et décembre il est de 0,21%/j (pour un poids individuel final de 59,9 g) pour les adultes, c'est le taux le plus faible que l'on ait rencontré depuis le début du REMONOR en 1998. Les indices de chair se maintiennent à des niveaux ...